A fuzzy approach to risk based decision making - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, T. (Springer-Verlag, 2006)
Decision making is a tough process. It involves dealing with a lot of uncertainty and projecting what the final outcome might be. Depending on the projection of the uncertain outcome, a decision has to be made. In a peer-to-peer financial interaction the trusting agent, in order to analyse the Risk, has to consider the possible likelihood of failure of the interaction and the possible consequences of failure to its resources involved in the interaction before concluding whether to interact with the probable trusted agent or not. Further, it may also have to choose and decide on an agent to interact with from a set of probable trusted agents. In this paper, we propose a fuzzy risk based decision making system that would assist the trusting agent to ease its decision making process.